2016
DOI: 10.1021/acs.est.5b06016
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Two Pharmaceuticals by the Ammonia-Oxidizing Archaeon Nitrososphaera gargensis

Abstract: The biotransformation of some micropollutants has previously been observed to be positively associated with ammonia oxidation activities and the transcript abundance of the archaeal ammonia monooxygenase gene (amoA) in nitrifying activated sludge. Given the increasing interest in and potential importance of ammonia-oxidizing archaea (AOA), we investigated the capabilities of an AOA pure culture, Nitrososphaera gargensis, to biotransform ten micropollutants belonging to three structurally similar groups (i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
80
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 51 publications
5
80
1
1
Order By: Relevance
“…Nitrifying bacteria, and, in particular, the enzyme ammonia monooxygenase (AMO), have previously been associated with micropollutant biotransformation. 10,[65][66][67][68][69] In fact, in our study, the increase in nitrifying activity in the range between 1 and 7 d SRT (Tables S4 and S5) coincided with the strongest increase in mean MP biotransformation rates. However, the biotransformation of many MPs that exhibited increasing trends were not or only slightly affected by inhibitors of nitrifying activity (e.g., acesulfame, ketoprofen, gemfibrozil or rufinamide in Table 1), suggesting that AMO is likely not the primary driver of increased biotransformation rate constants at higher SRTs for the majority of substances studied.…”
Section: Dependence Of Biotransformation Rate Constants On Srtsupporting
confidence: 59%
“…Nitrifying bacteria, and, in particular, the enzyme ammonia monooxygenase (AMO), have previously been associated with micropollutant biotransformation. 10,[65][66][67][68][69] In fact, in our study, the increase in nitrifying activity in the range between 1 and 7 d SRT (Tables S4 and S5) coincided with the strongest increase in mean MP biotransformation rates. However, the biotransformation of many MPs that exhibited increasing trends were not or only slightly affected by inhibitors of nitrifying activity (e.g., acesulfame, ketoprofen, gemfibrozil or rufinamide in Table 1), suggesting that AMO is likely not the primary driver of increased biotransformation rate constants at higher SRTs for the majority of substances studied.…”
Section: Dependence Of Biotransformation Rate Constants On Srtsupporting
confidence: 59%
“…The biotransformation capabilities of AOMs for several MPs, such as mianserin and ranitidine (Men et al, 2016), triclosan and bisphenol A (Roh et al, 2009), p-cresol (Kjeldal et al, 2014), and estrogens (i.e., E1, E2, E3 and EE2) (Khunjar et al, 2011;Shi et al, 2004;Skotnicka-Pitak et al, 2009) have been demonstrated by pure culture studies, whereas no biotransformation activity has been observed in AOM pure cultures for compounds such as ibuprofen (Shi et al, 2004), trimethoprim (Khunjar et al, 2011), and eight other pesticides and pharmaceuticals (Men et al, 2016). These pure culture studies provide fundamental insights into biotransformation capability, reaction types and mechanisms, and the potential formation of TPs, but no concrete conclusion on MP biotransformation by AOMs in NAS communities can be drawn if negative results were obtained in the pure culture studies.…”
Section: Introductionmentioning
confidence: 99%
“…Given the high dependency of AOA on copper, this inhibitory mechanism could provide a basis for developing approaches for modulating the composition of nitrifying communities in terrestrial, aquatic, and engineered environments. Keeping in mind that AOA have a lower N 2 O yield per mol ammonium oxidized than AOB [62], contribute to transformation of micropollutants [63], have greater adaptability to live in extreme environments than AOB [20], and possess a higher substrate affinity than AOB [18,19], such modulations might help to reduce greenhouse gas emissions from WWTPs and agricultural soils and could contribute to improved micropollutant transformation and ammonia effluent concentrations in various sewage treatments.…”
Section: Discussionmentioning
confidence: 99%